Microsatellite DNA marker analysis in brown mussels, Perna perna (Linnaeus, 1758) from the coastal waters of Oman - Al-Barwani, Said Mohammed Hilal; Aziz, D.; Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz (Academic Journals, 2013)
Thirteen highly polymorphic microsatellite primer pairs developed for Perna viridis from the gene bank were tested on 3 populations of Perna perna samples with the aim to adapt a fast, reliable method for preliminary screening and to genetically characterize the wild populations of P. perna in the Oman waters. The samples were collected from three different locations viz Ras Al-Had, Ras Madrakah and Mirbat. All primers showed high level of polymorphism for all populations. The mean observed heterozygosity was lower than the expected heterozygosity across the three populations which means there was a probability of inbreeding occurred in the populations. Both the chi-square (χ2) and likelihood (G2) ratio tests detected significant differences (p<0.05), which showed deviations from Hardy-Weinberg equilibrium. Cluster analysis revealed a close genetic relationship of P. perna between all populations and they were clustered according to their geographical origins into two major groups which include one cluster that grouped the Mirbat and the Ras Madrakah populations together while the other cluster showed the Ras Al Had domain. The highest genetic distance (1.2666) was observed between the Mirbat and the Ras Al Had populations while the lowest genetic distance (0.4746) was recorded between the Mirbat and Ras Madrakah populations. This study demonstrated that microsatellite markers with thirteen P. viridis primer pairs tested can be applied to genetically characterize the brown mussel populations in Oman waters.